Observational "go‐alongs" of follow‐up HIV care visits of two virally suppressed Black sexual minority men. Issue 1 (17th August 2021) - Dangerfield, Derek T.; Ober, Allison J.; Anderson, Janeane N.; Gorbach, Pamina; Bluthenthal, Ricky N.
Abstract: Purpose: This study explored potentially underreported healthcare contexts, clinical experiences, and motivations for adherence in care among virally suppressed Black sexual minority men (BSMM) living with HIV (LWHIV) in Baltimore, MD. Methods: Go‐alongs with two virally suppressed BSMM LWHIV supplemented 27 in‐depth interviews of a larger qualitative study guided by Positive Deviance and Life Course Theory. The go‐alongs involved accompanying participants' follow‐up HIV care visit to obtain a better account of contextual healthcare factors. Observations focused on (1) clinic location and resources, (2) sources of HIV and sexuality stigma or support in the clinic, and (3) patient‐provider interactions. Results: We found that facilitators and barriers to viral suppression for BSMM LWHIV included structural factors (i.e., healthcare setting, facility, and services), quality of patient‐provider interactions, and personal motivations to achieve viral suppression. Conclusion: Clinic accessibility, co‐located clinical services, and rapport with clinicians and healthcare staff could be key contextual conditions that facilitate retention in care among BSMM LWHIV.